The Effectiveness of Using English Songs on Students’ Listening Ability - Rawung, Meivi Theresya; Pelenkahu, Noldy; Liando, Nihta V. F (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research investigates the usefulness of music in improving auditory comprehension of second-grade students at SMP Negeri 2 Lirung. It employs a quantitative pre-experimental method, utilizing tests (pre-test and post-test) for data collection. The research involved 20 pupils from class VIII2. The findings reveal that incorporating songs significantly improved the pupils' listening abilities, the pre-test n-gain value fell in the low category with average scores rising from 51.25 on the pretest to the post-test n-gain value 81.50 on the posttest. The t-test results show a calculated value of ±4.5876, surpassing the critical value of ±2.101 at the 5% significance level. Thus, the hypothesis that using song media enhances students' listening skills (Ha) is accepted, whereas the hypothesis that it does not improve listening skills (HO) is rejected. Therefore, the research concludes that using English songs as a learning medium effectively enhanced the listening skills of students at SMP Negeri 2 Lirung.